2017
DOI: 10.1177/0363546517743720
|View full text |Cite
|
Sign up to set email alerts
|

Hip Arthroscopic Surgery With Labral Preservation and Capsular Plication in Patients With Borderline Hip Dysplasia: Minimum 5-Year Patient-Reported Outcomes

Abstract: While periacetabular osteotomy remains the standard for treating true acetabular dysplasia, hip arthroscopy may provide a safe and durable means of managing intra-articular abnormalities in the setting of borderline acetabular dysplasia at midterm follow-up. These procedures should be performed by surgeons with expertise in advanced arthroscopic techniques, using strict patient selection criteria, with emphasis on labral preservation and capsular plication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
138
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(141 citation statements)
references
References 45 publications
3
138
0
Order By: Relevance
“…E ven as experience with hip-preservation surgery has increased exponentially over the past decade, patients with mild or borderline dysplasia have remained a challenging group. Well-designed recent studies have demonstrated excellent results after arthroscopic surgery in these patients, 1,2 whereas others have demonstrated failure rates more than 30%. 3 Whether it is due to reports of good clinical outcomes, improved arthroscopic technologies, the technically demanding nature and increased morbidity of periacetabular osteotomy (PAO), or the high prevalence of concomitant cam deformity in dysplastic hips, 4 the use of hip arthroscopy in dysplastic patients has been increasing over recent years.…”
Section: See Related Article On Page 3240mentioning
confidence: 96%
“…E ven as experience with hip-preservation surgery has increased exponentially over the past decade, patients with mild or borderline dysplasia have remained a challenging group. Well-designed recent studies have demonstrated excellent results after arthroscopic surgery in these patients, 1,2 whereas others have demonstrated failure rates more than 30%. 3 Whether it is due to reports of good clinical outcomes, improved arthroscopic technologies, the technically demanding nature and increased morbidity of periacetabular osteotomy (PAO), or the high prevalence of concomitant cam deformity in dysplastic hips, 4 the use of hip arthroscopy in dysplastic patients has been increasing over recent years.…”
Section: See Related Article On Page 3240mentioning
confidence: 96%
“…54 In this case, labral repair and capsular plication should be performed when possible. 53,55 Given the varied clinical outcomes, hip arthroscopy should therefore be used with caution in the setting of dysplasia. Strong consideration should be given to PAO in the setting of DDH.…”
Section: Hip Arthroscopymentioning
confidence: 99%
“…Surgical management of borderline hip dysplasia is an area of multiple recent clinical investigations. 7,10,11,36,37 There is consensus that symptomatic mild and moderate/severe dysplasia is best treated with PAO with good clinical results. [12][13][14] Recent retrospective studies have evaluated clinical outcomes of hip arthroscopy in patients with borderline hip dysplasia.…”
Section: Operative Treatment Of Borderline Hip Dysplasiamentioning
confidence: 99%
“…8 The radiographic criteria for borderline hip dysplasia are variably defined in the literature. 4,6,[9][10][11] While there is general consensus that mild and moderate/severe hip dysplasia is best treated with PAO, [12][13][14] the efficacy and longevity of arthroscopic procedures for the treatment of borderline hip dysplasia are controversial. 15,16 In contrast, acetabular retroversion is characterized by excess anterior coverage of the femoral head by the acetabulum resulting in femoroacetabular impingement (FAI) and subsequent joint damage.…”
mentioning
confidence: 99%